2009
DOI: 10.1002/lsm.20672
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 1,450 nm diode laser on facial sebum excretion

Abstract: Background and Objective Laser therapy with a 1,450 nm diode laser is a clinically effective treatment for acne vulgaris, although the mechanism of action is unknown. To investigate this, we conducted a small, prospective, controlled clinical trial to assess this laser's effects on the facial sebum excretion rate (SER). Materials and Methods Fourteen healthy volunteers without active acne were enrolled in this study and received three laser treatments on test areas of the nose and forehead. Nine subjects compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 21 publications
(39 reference statements)
1
13
0
1
Order By: Relevance
“…An objective improvement was noted in sebum production, with a reduction of 20% to 27% on the forehead as measured using the Sebumeter as early as 3 weeks after the first treatment, although the positive effect on sebum reduction did not last for more than 1 month after treatment. No reduction in sebum production was observed on the nasolabial fold, which might be because of the difficulty in applying the IPL handpiece around the nasolabial fold and in performing Sebumeter measurement around the nose 20 …”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…An objective improvement was noted in sebum production, with a reduction of 20% to 27% on the forehead as measured using the Sebumeter as early as 3 weeks after the first treatment, although the positive effect on sebum reduction did not last for more than 1 month after treatment. No reduction in sebum production was observed on the nasolabial fold, which might be because of the difficulty in applying the IPL handpiece around the nasolabial fold and in performing Sebumeter measurement around the nose 20 …”
Section: Discussionmentioning
confidence: 87%
“…No reduction in sebum production was observed on the nasolabial fold, which might be because of the difficulty in applying the IPL handpiece around the nasolabial fold and in performing Sebumeter measurement around the nose. 20 Santo used a 3-hour incubation period in a comparative split-face study of topical ALA plus IPL versus IPL alone performed twice, 2 weeks apart, for the treatment of acne. 21 Thirteen of 15 patients completed the study, and all showed apparent improvement on both sides of the face.…”
Section: Discussionmentioning
confidence: 99%
“…First, we performed two sessions of a nonablative 1450-nm diode laser to decrease sebum output, in order to eliminate a variable which has proven to be associated with enlarged pores. Although Laubach et al (6) recently reported that three 1450-nm laser treatment sessions did not cause marked changes in the sebum excretion rate compared to that of the control, non-ablative infrared lasers, such as 1450-nm diode lasers, have been suggested to cause thermal damage to sebaceous glands and reduce sebum production (7,8).…”
Section: Discussionmentioning
confidence: 95%
“…Recent studies have demonstrated the safety and efficacy of a commercially available laser with this wavelength (Smoothbeam, Candela, Wayland, MA) for the treatment of mild to moderate inflammatory acne by significantly reducing lesion counts; the device received FDA approval for this use in 2003 14 …”
Section: Discussionmentioning
confidence: 99%